Occupational Risk Factors for Hoarseness Among Police Officers in Finland - Putus, Tuula (Elsevier Inc., 2025)
Purpose
Police officers have many work-related risks. In Finland, hoarseness and other respiratory symptoms and related risk factors have not been investigated on a national level. In many of the work tasks carried out by the police, an excellent physical and mental condition is essential.
Method
Our aim was to determine the prevalence of hoarseness and related respiratory symptoms and to investigate eventual occupational risk factors associated with hoarseness. We also compared different work tasks and remediation procedures in three police stations with indoor air problems.
Material
In all, 767 persons completed a nation-wide e-mail survey. The study population is approximately 11% of the total police force in Finland. Half of the study population were men. In three cities, we evaluated the outcome of different type of remediation methods after the moisture damaged buildings were renovated. The prevalence of hoarseness was compared in different work tasks and the risk associated with indoor air, work-related stress, and background factors were estimated. Information on the remediation was obtained from the employer.
Results
Altogether, 30.5% of the respondents had hoarseness and 15.5% had work-related stress. Almost 9% were smokers and 43% had pets at home. Of all the respondents, 13% had asthma. Hoarseness was not related to work-related stress. The strongest risk factors for hoarseness were asthma and exposure to mold odor, dusts and cold temperatures after adjusting for age, gender, smoking and pet-owning. When three renovation techniques were compared, the best results were found in the building with a thorough remediation and the removal of mold from the building.
Conclusions
We conclude that the exposure to irritant gases, fumes, and bioaerosols should be minimized whenever possible in order to avoid incident asthma and voice problems.